Apresentação De Alguns Dos Aspectos Ambientais E Econômicos A Cerca Dos Veículos Elétricos: Análise Do Impacto Socioambiental E Viabilidade Econômica - Barros, Luis Otávio Oliveira (Universidade Federal do Tocantins, 2022)
This paper consists of a bibliographical study to determine possible reasons and difficulties for the competitive insertion of electric cars, analyzing aspects such as the influence of infrastructure and prices that involve the implementation of this market in Brazil. With the presentation of some concepts to contextualize and familiarize the reader with the research object, and questions about energy efficiency, environmental impacts, economic impacts, sustainable progress and the perspective for the future of technology.